2011
DOI: 10.1037/a0025613
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating conditional release in female insanity acquittees: A risk management perspective.

Abstract: Research focusing on insanity acquittees released into the community has been growing at an exponential rate to reflect the policy and practice of placing these individuals in the community under supervision. Research on females placed on conditional release has lagged behind studies on males. Data on 76 females (M age = 42.76) found not guilty by reason of mental disease or defect and conditionally released over a 7-year time period were evaluated. Fifty-two females (68.4%) maintained their conditional releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…Other studies have found similar results using multivariate outcomes with the metric of emerging mental health symptoms requiring hospitalization (Parker, 2004; Vitacco et al ., 2008, 2011), which could be considered a dynamic risk counterpart to the finding by Bertman-Pate et al . Previous criminal charges have also been shown to be related to revocation by Vitacco and colleagues (2013).…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Other studies have found similar results using multivariate outcomes with the metric of emerging mental health symptoms requiring hospitalization (Parker, 2004; Vitacco et al ., 2008, 2011), which could be considered a dynamic risk counterpart to the finding by Bertman-Pate et al . Previous criminal charges have also been shown to be related to revocation by Vitacco and colleagues (2013).…”
Section: Discussionsupporting
confidence: 52%
“…For convenience and ease of discussion, the variables were classified based on the type of variable under consideration (i.e., demographic, clinical/diagnostic, legal, and program), consistent with previous studies of conditional release (Callahan & Silver, 1998; Monson et al ., 2001; Vitacco et al ., 2008, 2011, 2013). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Return to hospital often reflects a deterioration in the individual's mental health status (Bertman‐Pate et al, ; Golding, Eaves, & Kowaz, ; Vitacco et al, ), a failure to comply with treatment (Bertman‐Pate et al, ; Golding et al, ), and substance use (Bertman‐Pate et al, ; Callahan & Silver, ; Golding et al, ; Riordan et al, ). A recent study by Vitacco and colleagues () on CD revocation among 76 female American insanity acquittees found that demographic, diagnostic, mental health, and criminal history characteristics were unrelated to conditional release outcomes (dichotomized to reflect successful maintenance of CD (68.4%) or return to hospital (31.6%) over a 24 month period). Short‐term hospitalization was the only factor associated with revocation of conditional release.…”
Section: What Predicts Success or Failure On Conditional Discharge?mentioning
confidence: 99%